Food handling practice and associated factors among food handlers in public food establishments of Ethiopia: a systematic review and meta-analysis - Maru Meseret Tadele; Amare Dagnaw; Dehabo Alamirew (BMJ Open)
Objectives Food handlers are individuals who are involved in food preparation, storage or service of food in a food facility. Unless they keep their personal hygiene, they are highly responsible for contaminating food or transmitting microbes to consumers. Thus, the main aim of this review was to pool the level of good food handling practice among food handlers working in public food establishments in Ethiopia.Design A systematic review and meta-analysis using the Joanna Briggs Institute (JBI) Critical Appraisal tool.Data sources PubMed, Google Scholar and Advanced Google were searched up to the end of February 2021.Eligibility criteria for selecting studies Publication status, publication language, type of study participants and the type of article were used to screen the article.Data extraction and study quality assessment All reviewers collected data independently and merged them together. A tool called the JBI Meta-Analysis of Statistics Assessment and Review Instrument was used to assess the quality of each research article. The assessment was performed by two reviewers.Result A total of 16 research articles were included in the review. The pooled level of good food handling practice was 50.72% with 95% CI (43.84% to 57.6%). Training (adjusted OR (AOR)=3.4, 95% CI (2.33 to 4.95)), attitude (AOR=3.62, 95% CI (2.23 to 5.85)) and medical check-up (AOR=5.12, 95% CI (2.93 to 8.95)) were identified as factors affecting good food handling practice with 95% CI at p<0.05.Conclusion The level of good food handling practice among food handlers working in public food establishments of Ethiopia was very low compared with literature, and variables such as food handler training, attitude towards good food handling practice and the existence of regular medical check-ups were factors affecting good food handling practice. Provision of training that could change the attitude and regular medical check-ups for food handlers has to be in place.